PENGARUH BRAND IMAGE, PRODUCT QUALITY, DAN HEDONIC LIFESTYLE TERHADAP PURCHASE DECISION IPHONE DI KOTA JEPARA - Marcello Hata Arswenda; Nurul Huda (Jurnal Bina Bangsa Ekonomika, 2024)
The study was conducted to analyze the influence of the variables Brand Image (X1), Product Quality (X2), and Hedonic Lifestyle (X3) on the dependent variables of Purchase Decision (Y) consumers of Iphone Users in Jepara City. Primary data were used in this study by collecting data through observation with questionnaires. The data collection methodology uses an accidental sampling method survey with the ancient rao formula with a result of 96.04 rounded to 100. The respondents of the study were smartphone users from the Jepara city iphone brand. The results show that brand image has a significant positive influence on purchase decisions, product quality has a positive and significant influence on purchase decisions, and hedonic lifestyle has a significant positive influence on purchase decisions. Simultaneously, the variables of brand image, product quality, and hedonic lifestyle have a significant positive influence on purchase decisions